Latanoprost niosomes as a sustained release ocular delivery system for the management of glaucoma. (3rd May 2020) - Fathalla, Dina; Fouad, Ehab A.; Soliman, Ghareb M.
Abstract: Objective: Glaucoma is a leading cause of irreversible blindness worldwide. Whereas latanoprost is one of the most effective drugs in glaucoma treatment, its eye drops need frequent application leading to lack of patient adherence. This study aimed to develop a patient-friendly niosome-in-gel system for the sustained ocular delivery of latanoprost. Methods: Niosomes were prepared by the reverse-phase evaporation technique and optimized for different formulation parameters, such as cholesterol/surfactant and drug/surfactant ratios. Selected niosomal formulations were incorporated into different gels and their viscosity and drug release kinetics were evaluated. Optimal niosomal gel was evaluated in vivo in rabbits' eyes for irritation potential and ability to reduce intraocular pressure. Results: FT-IR studies showed that there were nonspecific interactions between latanoprost and different niosomal components leading to drug encapsulation efficiency ≥88%. Latanoprost encapsulation efficiency increased with the drug/surfactant ratio and encapsulation efficiency ∼98% was obtained at a ratio of 50%. Pluronic ® F127 had the best ability to sustain drug release from the niosomes. In rabbits' eyes, this gel was free of toxic and irritant effects and reduced intraocular pressure over a period of three days, which was significantly longer than that of commercial latanoprost eye drops. Conclusion: Latanoprost niosomal Pluronic ® F127 gel may find applications in glaucoma management.